HLA-C promotes proliferation and cell cycle progression in trophoblast cells. (16th February 2021) - Lv, Hong; Zhou, Qian; Li, Lie; Wang, Shan
Abstract: Objectives: The development of maternal-fetal immune tolerance and adequate trophoblast function are essential for the establishment and maintenance of pregnancy. Human leukocyte antigen (HLA), the major histocompatibility complex (MHC) antigen specific to humans, plays an important role in placentation and is involved in many pregnancy-associated diseases. HLA-C is the only classical MHC I gene expressed at the maternal-fetal interface. To investigate whether HLA-C plays an independent role in regulating the development of trophoblasts, we explored the effect of HLA-C expression on placental development. Methods: The role of HLA-C in the growth and migration of trophoblast JAR and HTR-8/Svneo cell lines was investigated after HLA-C-expressing lentivirus transfection. Results: The MTT assay and colony formation assay showed that HLA-C promoted cell proliferation. Furthermore, cell cycle analysis showed that HLA-C overexpression accelerated the transition of trophoblast cells from the G0/G1 phase to the S phase. However, FACS analysis and migration assay indicated that HLA-C had no significant influence on trophoblast apoptosis and migration. Conclusion: Our study demonstrated for the first time that besides being involved in immune tolerance, HLA-C can directly promote placental growth without interacting with immune cells, which could provide a new insight into studying the functions of HLA-C at the maternal-fetal interface.